1984
DOI: 10.1016/0165-1781(84)90031-3
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of REM latency, dexamethasone suppression, clonidine, and apomorphine tests as biological markers of endogenous depression: A pilot study

Abstract: In a sample of 12 major depressive inpatients, endogenous subtype (8 primary and 4 secondary) defined by Research Diagnostic Criteria, we compared the sensitivity of four potential biological markers: latency of rapid eye movement (REM) sleep (recorded during at least 4 consecutive nights), dexamethasone suppression, and the clonidine and apomorphine tests. Shortened REM latency (less than 50 minutes during at least 1 night) identified 67% of depressives (87% of primary and 25% of secondary); nonsuppression af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…In particular, intra-and inter-assay coefficients of variation were, respectively, 13.3 and 14.8% for GH (Franchimont 1968); 10.0 and 10.0% for prolactin (Franchimont 1969); 4.3 and 8.3% for cortisol (Ansseau et al 1984). All samples were processed in duplicate within the same assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, intra-and inter-assay coefficients of variation were, respectively, 13.3 and 14.8% for GH (Franchimont 1968); 10.0 and 10.0% for prolactin (Franchimont 1969); 4.3 and 8.3% for cortisol (Ansseau et al 1984). All samples were processed in duplicate within the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Hormone assays GH, prolactin, cortisol, and ACTH were measured by radioimmunoassay (RIA), according to previously published methods (Franchimont 1968;Ansseau et al 1984). In particular, intra-and inter-assay coefficients of variation were, respectively, 13.3 and 14.8% for GH (Franchimont 1968); 10.0 and 10.0% for prolactin (Franchimont 1969); 4.3 and 8.3% for cortisol (Ansseau et al 1984).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with a basal systolic blood pressure less than 100 mmHG were excluded from the study. Moreover, in order to be included, patients had to present a basal (t0) GH level less than 5 ng/mL before the pharmacological challenge [3]. The exclusion of subjects with basal GH values > 5 ng/mL was recommended by Laakman [11], who demonstrated that 'presimulator' healthy volunteers responded significantly less to a noradrenergic challenge than healthy volunteers with low basal values.…”
Section: Subjectsmentioning
confidence: 99%
“…Although shortened REM latency is found more frequently than is HPA hyperactivity (Annseau et al 1984;Feinberg and Carroll 1984;Giles et al 1987;Kerkhofs et al 1986;Kupfer et al 1984;Mendlewicz et al 1984;Rush et al 1982;Rush et al 1983), both abnormalities can occur simultaneously in the same patients. Furthermore, subjects showing the shortest REM latency also manifest the greatest degree of HPA activity, so that an inverse relationship between these two parameters has been observed (Asnis et al 1983;Shipley et al 1989).…”
Section: Introductionmentioning
confidence: 99%